2022
DOI: 10.1200/op.22.00173
|View full text |Cite
|
Sign up to set email alerts
|

Communication About Fall Risk in Community Oncology Practice: The Role of Geriatric Assessment

Abstract: PURPOSE: Falls are a modifiable source of morbidity for older adults with cancer, yet are underassessed in oncology practice. In this secondary analysis of a nationwide cluster-randomized controlled trial, we examined characteristics associated with patient-oncologist conversations about falls, and whether oncologist knowledge of geriatric assessment (GA) resulted in more conversations. METHODS: Eligible patients (ClinicalTrials.gov identifier: NCT02107443 ) were age ≥ 70 years, had stage III/IV solid tumor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Finally, in the intervention group, caregivers were more satisfied with communication after the visit (difference, 1.05 [95% CI, 0.12 to 1.98]; P = .03). Two recently published secondary analyses of data from COACH reported that, compared to usual care, providing oncologists with a GA summary with tailored recommendations was associated, respectively, with an increase in oncologist-initiated conversations concerning physical performance and functional status with corresponding recommendations to address these concerns 36 ; and with an increased number of conversations regarding comorbidities per patient, with having a greater number of concerns acknowledged, and with a greater chance of having those comorbidity concerns addressed. 26…”
Section: Updated Recommendationsmentioning
confidence: 99%
“…Finally, in the intervention group, caregivers were more satisfied with communication after the visit (difference, 1.05 [95% CI, 0.12 to 1.98]; P = .03). Two recently published secondary analyses of data from COACH reported that, compared to usual care, providing oncologists with a GA summary with tailored recommendations was associated, respectively, with an increase in oncologist-initiated conversations concerning physical performance and functional status with corresponding recommendations to address these concerns 36 ; and with an increased number of conversations regarding comorbidities per patient, with having a greater number of concerns acknowledged, and with a greater chance of having those comorbidity concerns addressed. 26…”
Section: Updated Recommendationsmentioning
confidence: 99%